Periodontal Disease and Adverse Neonatal Outcomes: A Systematic Review and Meta-Analysis - Zhang, Youzhen; Feng, Wanbing; Li, Jingyu; Cui, Linlin; Chen, Zi-Jiang (Frontiers in Pediatrics, 2022)
Objective: To evaluate the association between maternal periodontal disease (PD) and three main adverse neonatal outcomes: preterm birth (PTB), low birth weight (LBW), and small for gestational age (SGA). Methods: The Ovid Medline, Web of Science, Embase, Cochrane Library were searched up to December 6, 2020, for relevant observational studies on an association between periodontal disease and risk of preterm birth (PTB), low birth weight (LBW), and small for gestational age (SGA). Eligibility criteria included observational studies which compared the prevalence of PTB and/or LBW and/or SGA between PD women and periodontal health controls. The Exclusion criteria included incomplete data, animal research, mixing up various pregnancy outcomes, such as “preterm low birth weight”, and languages other than Chinese and English. Data was extracted and analyzed independently by two authors. The meta-analysis was performed using Stata Statistical Software, Release 12 (StataCorp LP, College Station, TX, USA). Odds ratio (OR), confidence intervals (CIs), and heterogeneity (I2) were computed. Result(s): Fourteen case-control studies and 10 prospective cohort studies, involving 15278 participants, were identified. Based on fixed effect meta-analysis, PTB showed a significant association with PD (OR=1.57, 95% CI: 1.39-1.77, P＜0.00001), LBW also showed a significant association with PD (OR=2.43, 95% CI: 1.75-3.37, P＜0.00001) in a random effect meta-analysis. However, a random effect meta-analysis showed no relationship PD and SGA (OR=1.62, 95% CI: 0.86-3.07, P=0.136). Conclusion(s): Our findings indicate that pregnant women with PD have a significantly higher risk of PTB and LBW. However, large prospective, blinded cohort studies with standardized diagnostic criteria of PD and adequate control of confounding factors are still required to confirm the relationship between PD and adverse neonatal outcomes.